Village malaria worker performance key to the elimination of artemisinin-resistant malaria: a Western Cambodia health system assessment - Sara E. Canavati; Saranath Lawpoolsri; Cesia E. Quintero; Chea Nguon; Po Ly; Sasithon Pukrittayakamee; David Sintasath; Pratap Singhasivanon; Koen Peeters Grietens; Maxine Whittaker (2016)
Village malaria workers (VMWs) and mobile malaria workers (MMWs) are a critical component of Cambodia's national strategy to eliminate Plasmodium falciparum malaria by 2025. Since 2004, VMWs have been providing malaria diagnosis through the use of rapid diagnostic tests and free-of-charge artemisinin-based combination therapy in villages more than 5 km away from the closest health facility. They have also played a key role in the delivery of behaviour change communication interventions to this target population. This study aimed to assess the job performance of VMWs/MMWs, and identify challenges they face, which may impede elimination efforts. A mixed-methods assessment was conducted in five provinces of western Cambodia. One hundred and eighty five VMW/MMW participants were surveyed using a structured questionnaire. Qualitative data was gathered through a total of 60 focus group discussions and 65 in-depth interviews. Data triangulation of the qualitative and quantitative data was used during analysis. Overall, VMWs/MMWs met or exceeded the expected performance levels (80 %). Nevertheless, some performance gaps were identified. Misconceptions regarding malaria transmission and prevention were found among workers. The recommended approach for malaria treatment, directly-observed treatment (DOT), had low implementation rates. Stock-outs, difficulties in reaching out to migrant and mobile populations, insufficient means of transportation and dwindling worker satisfaction also affected job performance. VMW/MMW job performance must be increased from 80 to 100 % in order to achieve elimination. In order to do this, it is recommended for the national malaria programme to eliminate worker malaria knowledge gaps. Barriers to DOT implementation and health system failures also need to be addressed. The VMW programme should be expanded on several fronts in order to tackle remaining performance gaps. Findings from this evaluation are useful to inform the planning of future activities of the programme and to improve the effectiveness of interventions in a context where artemisinin drug resistance is a significant public health issue.